HERMENEUTIK FEMINIS KEPEMIMPINAN DAN SOLIDARITAS PEREMPUAN MENURUT MARIA, DEBORA, RUT - Hadi Prasetyo; Ruben Nesimnasi (STT Ekklesia Pontianak, 2026)
Abstract: This study aims to develop Elisabeth Schüssler Fiorenza's feminist hermeneutics (suspicion, memory, and liberation) to reread the stories of Mary (Luke 1:46-55), Deborah (Judges 4-5), and Ruth (Book of Ruth) as sources of inspiration for women's leadership and solidarity in the patriarchal context of the Indonesian church and society. This qualitative library research identifies a gap: previous studies only discuss one figure or use a partial feminist approach, without reconstructing an integrative and contextual model. Through three steps of feminist hermeneutics, this study reveals that patriarchal interpretations have domesticated Mary as a passive figure, viewed Deborah's leadership as a